2017
DOI: 10.1212/cpj.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Sharing notes with patients

Abstract: Improved patient engagement is a critical consideration in the new payment climate. Releasing progress notes for patients to view may improve patient involvement and engagement in their care. Patients perceive benefit from viewing physician progress notes. As initial studies involved only primary care physicians, specialist physicians may have specific considerations when releasing notes to patients. This article provides a framework for neurologists to implement a note release policy in their practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Although few studies found that physicians perceived a loss of autonomy when patients became more knowledgeable [ 43 ] or addressed the issue of merging the physicians’ aspiration for autonomy with the concept of informed decision making [ 44 ], research on GPs’ professional values and their compatibility with open health records is still pending. Even though identified conditions for an implementation of open records were reported previously [ 45 - 47 ], considering the physicians’ attitudes based on their professional self-conception has not yet been researched.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies found that physicians perceived a loss of autonomy when patients became more knowledgeable [ 43 ] or addressed the issue of merging the physicians’ aspiration for autonomy with the concept of informed decision making [ 44 ], research on GPs’ professional values and their compatibility with open health records is still pending. Even though identified conditions for an implementation of open records were reported previously [ 45 - 47 ], considering the physicians’ attitudes based on their professional self-conception has not yet been researched.…”
Section: Discussionmentioning
confidence: 99%